CHARACTERISTICS OF THE NUTRITIONAL AND METABOLIC STATUS IN PATIENTS WITH TUBO-PERITONEAL FACTOR OF INFERTILITY AND OBESITY - Тамара Владимировна Жук; Светлана Дмитриевна Яворская; Вячеслав Валерьевич Востриков (The Publishing House Medicine and Enlightenment, 2022)
Assisted reproductive technologies (ART) offer hope to infertile couples and are the most common method to overcome infertility and achieve pregnancy. However, the primary objective of ART is not the fact of pregnancy, but safe delivery of a healthy child. Obesity is one of the unresolved problems affecting fertility and reducing the effectiveness of ART programs. Obesity is a comorbidity characterized by impaired lipid and carbohydrate metabolism, increased oxidative stress and the level of pro-inflammatory cytokines, as well as impaired vitamin and mineral status. The diagnosing of typical metabolic and nutritional disorders in patients with infertility and obesity will enable to develop general recommendations for individual programs of pregravidar preparation. The aim of the studye research was to evaluate the levels of vitamin D, homocysteine, ferritin, markers of oxidative stress and inflammation, as well as markers of carbohydrate and lipid metabolism in patients with tubo-peritoneal infertility and obesity. Materials and methods. The study included 53 patients with tubo-peritoneal infertility planning IVF. The patients were divided into two groups, according to the body mass index: group 1 included 25 patients with BMI ≥ 30; group 2 comprised 28 patients with BMI = 18.5-24.9. All patients had venous blood test on an empty stomach to be determined the level of oxidative stress markers (8-OH-2-deoxyguanosine (8-OHdG)), the antioxidant system (total antioxidant capacity), C reactive protein, some indicators of the nutritional status, as well as insulin, glucose, glycosylated hemoglobin, lipid profile (cholesterol, triglycerides, LDL, HDL) in the serum. Research results. Patients with obesity and tubo-peritoneal infertility, compared with the patients having normal body weight, presented a special «metabolic status» characterized by the disorder of the nutritional balance, as well as the disorder of lipid, carbohydrate and oxidative metabolism.